Implant Platform Switching: Biomechanical Approach Using Two-Dimensional Finite Element Analysis - Tabata, Lucas Fernando [UNESP]; Assunção, Wirley Goncalves [UNESP]; Ricardo Barao, Valentim Adelino [UNESP]; Sousa, Edson Antonio Capello [UNESP]; Gomes, Erica Alves [UNESP]; Delben, Juliana Aparecida [UNESP] (Lippincott Williams & Wilkins, 2010)
In implant therapy, a peri-implant bone resorption has been noticed mainly in the first year after prosthesis insertion. This bone remodeling can sometimes jeopardize the outcome of the treatment, especially in areas in which short implants are used and also in aesthetic cases. To avoid this occurrence, the use of platform switching (PS) has been used. This study aimed to evaluate the biomechanical concept of PS with relation to stress distribution using two-dimensional finite element analysis. A regular matching diameter connection of abutment-implant (regular platform group [RPG]) and a PS connection (PS group [PSG]) were simulated by 2 two-dimensional finite element models that reproduced a 2-piece implant system with peri-implant bone tissue. A regular implant (prosthetic platform of 4.1 mm) and a wide implant (prosthetic platform of 5.0 mm) were used to represent the RPG and PSG, respectively, in which a regular prosthetic component of 4.1 mm was connected to represent the crown. A load of 100 N was applied on the models using ANSYS software. The RPG spreads the stress over a wider area in the peri-implant bone tissue (159 MPa) and the implant (1610 MPa), whereas the PSG seems to diminish the stress distribution on bone tissue (34 MPa) and implant (649 MPa). Within the limitation of the study, the PS presented better biomechanical behavior in relation to stress distribution on the implant but especially in the bone tissue (80% less). However, in the crown and retention screw, an increase in stress concentration was observed.
Keywords: Dental implants; platform switching; implant supported prosthesis; finite element analysis; stress distribution; crestal bone loss